2018
DOI: 10.3171/2017.2.jns162951
|View full text |Cite
|
Sign up to set email alerts
|

Isolated abducens nerve palsy associated with subarachnoid hemorrhage: a localizing sign of ruptured posterior inferior cerebellar artery aneurysms

Abstract: OBJECTIVE Compressive cranial nerve syndromes can be useful bedside clues to the diagnosis of an enlarging intracranial aneurysm and can also guide subsequent evaluation, as with an acute oculomotor nerve (cranial nerve [CN] III) palsy that is presumed to be a posterior communicating artery aneurysm and a surgical emergency until proven otherwise. The CN VI has a short cisternal segment from the pontomedullary sulcus to Dorello's canal, remote from most PICA aneurysms but in the hemodynamic pathway of a ruptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…[6] A range of aneurysms, including those affecting the PICA, ICA, Acom, posterior communicating artery, and middle cerebral artery aneurysms, hold the potential to impact the abducent nerve function. [1,3,5,10] According to the findings of our study, a noteworthy association has been established between the abducent nerve and ruptured PICA aneurysms. While, in the context of unruptured aneurysms, a statistically significant correlation has been identified between the abducent nerve palsy and factors such as the cavernous location, and dome size.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…[6] A range of aneurysms, including those affecting the PICA, ICA, Acom, posterior communicating artery, and middle cerebral artery aneurysms, hold the potential to impact the abducent nerve function. [1,3,5,10] According to the findings of our study, a noteworthy association has been established between the abducent nerve and ruptured PICA aneurysms. While, in the context of unruptured aneurysms, a statistically significant correlation has been identified between the abducent nerve palsy and factors such as the cavernous location, and dome size.…”
Section: Discussionsupporting
confidence: 73%
“…is aligns with the work of Burkhardt et al, who investigated 13 patients with 6 th nerve palsy from a broader cohort of 106 patients displaying PICA aneurysms. [1] e researchers suggest the abducent nerve palsy as a potential localizing sign for a ruptured PICA aneurysm. However, considering that the sample size could pose limitations to drawing definitive conclusions.…”
Section: Correlation Between Abducent Nerve Palsy and Ruptured Intrac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although abducens nerve was not directly adjacent to PICA, ruptured PICA aneurysm could result in isolated abducens nerve palsy, which was possibly associated with the hemodynamics of aneurysmal rupture instead of direct compression 58 . Burkhardt et al demonstrated ruptured PICA aneurysm was an independent risk factor of abducens nerve palsy 59 . Giant aneurysms might be misdiagnosed as tumors of posterior fossa due to similar symptoms and imaging features which were sometimes indistinguishable even with magnetic resonance angiography (MRA) and digital subtraction angiography (DSA) 46 , 47 .…”
Section: Aneurysmmentioning
confidence: 99%
“…Another case report underscores the importance of neuroimaging even in cases of isolated abducens nerve palsy, as CT angiography revealed a ruptured posterior inferior cerebellar artery (PICA) aneurysm and subarachnoid hemorrhage [ 13 ]. A retrospective study establishes a localizing relationship between isolated abducens nerve palsy, subarachnoid hemorrhage, and an underlying ruptured PICA aneurysm [ 14 ]. Hence, isolated abducens nerve palsy should not be overlooked, and appropriate neuroimaging should be considered.…”
Section: Discussionmentioning
confidence: 99%